2018
DOI: 10.1080/15299716.2018.1431169
|View full text |Cite
|
Sign up to set email alerts
|

“I never felt like there was a place for me:” Experiences of Bisexual and Pansexual Individuals with a Christian Upbringing

Abstract: Popular and scholarly literature describes the conflicts experienced by some gay and lesbian Christians, but less is known about the unique experiences of bisexual and pansexual populations. The purpose of this study was to understand the process by which bisexual and pansexual individuals with a Christian upbringing resolved conflict between sexual identity and religious beliefs. Grounded theory analysis of 17 interviews revealed a fluid and multidimensional process of resolution, which was influenced by comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Our findings align with the existing literature on the religion and spirituality of LGBT individuals. Like our participants, LGBT individuals in other studies have described early faith and church experiences that were negative and traumatic, including discrimination and lack of acceptance (Brennan-Ing et al, 2013;Cockayne et al, 2020;Hansen & Lambert, 2011;Levy & Edmiston, 2014;Levy & Harr, 2018;Murr, 2013;Wood & Conley, 2014). Likewise, individuals often describe difficult family relationships (Dahl & Galliher, 2012a;Foster et al, 2015;Levy & Edmiston, 2014;Page et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our findings align with the existing literature on the religion and spirituality of LGBT individuals. Like our participants, LGBT individuals in other studies have described early faith and church experiences that were negative and traumatic, including discrimination and lack of acceptance (Brennan-Ing et al, 2013;Cockayne et al, 2020;Hansen & Lambert, 2011;Levy & Edmiston, 2014;Levy & Harr, 2018;Murr, 2013;Wood & Conley, 2014). Likewise, individuals often describe difficult family relationships (Dahl & Galliher, 2012a;Foster et al, 2015;Levy & Edmiston, 2014;Page et al, 2013).…”
Section: Discussionmentioning
confidence: 51%
“…The literature on religion and spirituality in LGBT individuals highlights some common outcomes for LGBT individuals of all ages. For instance, LGBT individuals of all ages have both positive and negative experiences with their faith communities, and report coping with negative experiences by developing personal belief systems, finding affirming congregations, and reducing participation in non-affirming faith communities (Dunn & Creek, 2015;Foster et al, 2015;Levy & Edmiston, 2014;Levy & Harr, 2018;Porter et al, 2013). In a study with older adult LGBT individuals, Brennan-Ing et al (2013) found similar outcomes.…”
Section: Religion and Spirituality In Lgbt Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting the current state of play, this under-representation is demonstrated in several extensive volumes on sexuality and religion such as Boisvert and Daniel-Hughes (2016), Hunt (2015), Hunt and Yip (2012) and Taylor and Snowdon (2014). Indeed, research in this field that exclusively examines bisexuality, religion and spirituality is few and far between, with notable exceptions such as recent works by Levy and Harr (2018), Robinson (2015), Shepherd (2018) and Toft (2012Toft ( , 2014. In many ways, this is unsurprising.…”
Section: Mixing Bisexuality Religion and Spirituality: Muddling The Waters?mentioning
confidence: 99%
“…This is particularly axiomatic within Abrahamic religious spaces, leading to experiences of tension and conflict amongst bisexual religious actors (e.g. Levy and Harr, 2018;Shepherd, 2018). However, other religious and spiritual spaces such as Paganism and New Age seem to offer a more conducive and nurturing environment for the exploration and accommodation of ambiguity and fluidity that bisexuality imbues (e.g.…”
Section: Mixing Bisexuality Religion and Spirituality: Muddling The Waters?mentioning
confidence: 99%